Pengembangan Media Ajar Website Berbasis Pendekatan Saintifik Learning pada Materi Regulasi Kelas XI - Putri, Pristy Karunia; Rahmadina, Rahmadina (JOEAI (Journal of Education and Instruction), 2026)
This study aims to develop website-based instructional media using a scientific learning approach on regulation material for eleventh-grade students that is valid, practical, and effective for use in the learning process. The research method employed is Research and Development (R&D) using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The developed website-based instructional media includes regulation materials, learning activities based on the scientific approach (observing, questioning, experimenting, reasoning, and communicating), interactive practice exercises, and links to instructional videos to support students’ understanding. The feasibility of the media was evaluated through validation by subject-matter experts and media experts, as well as limited trials with eleventh-grade students. The validation results indicate that the website-based instructional media is categorized as highly feasible for use in learning. Students’ responses show that the website-based instructional media is easy to use, engaging, and helps improve students’ understanding of regulation material. Therefore, the website-based instructional media using a scientific learning approach can serve as an innovative and effective alternative learning medium to support the learning process.   Keywords: ADDIE, Webssite-Based Learning Media, Scientific Approach, Regulation, Research and Development (R&D)